Investment in Fixed Capital and the Stability of Growth Equilibrium - Inada, Ken-ichi (Review of Economic Studies, 1966)
Journal Article Investment in Fixed Capital and the Stability of Growth Equilibrium Get access Ken-ichi Inada Ken-ichi Inada Tokyo Metropolitan University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 1, January 1966, Pages 19–30, https://doi.org/10.2307/2296637 Published: 01 January 1966